Past Master Series: Jaber ibn Hayyan - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2008)
Jaber ibn Hayyan, became an alchemist at the court of Caliph Harun al-Rashid, for the whome he wrote the Kitab al-Zuhra ("Book of Venus" on "the nobel art of alchemy").